Tuning the mechanical properties of nanoglass-metallic glass composites with brick and mortar designs. (15th March 2021) - Yuan, Suyue; Branicio, Paulo S.
Abstract: We use molecular dynamics simulations to characterize the tensile deformation and failure of metallic glass (MG)-nanoglass (NG) composites designed with a brick and mortar architecture consisting of a 3 nm-grain-size NG matrix and a MG second phase. Results show that the overall strength of the matrix is significantly improved by the second phase without sacrificing the large NG matrix ductility. The mechanical synergy of the two phases is optimized by arranging the MG bricks in a staggered way, which effectively delocalizes the plastic deformation, hindering the buildup of local stress hot spots and the generation of critical shear bands. Graphical abstract: Image, graphical abstract